Microfracture for treatment of knee cartilage defects in children and adolescents - Gian M. Salzmann; Bert-Ram Sah; Hagen Schmal; Philip Niemeyer; Norbert P Sudkamp (MDPI AG, 2012)
Even though operative microfracture is the most frequent method for treatment of limited knee joint cartilage lesions among adults, data about ouctome in children and adolescents are rare. We performed a retrospective chart review and telephone interview to analyze for the clinical outcome following knee joint cartilage defect microfracturing among 10 children. Mean postoperative Lysholm was 92.1±9.9 and Tegner was 7.0±1.9. Clinical outcome differed across knee joint regions, as well as in dependence of varying pre-operative symptom duration, although this was not significant. Regression analysis did not reveal a significant impact of patient or defect characteristics on clinical outcome. Arthroscopic microfracturing for treatment of limited size symptomatic knee joint cartilage defects among children and adolescents is considered a reasonable surgical option. However, long-term outcome and larger patient cohorts are required.